Immunopathological Responses to the Bovine Mastitis Associated with Staphylococcus Species Infection - Al-Rasheed, Agharid A; Ahmed, Sana’a S; Al-Jashamy, Karim A; Garba, Bashiru (The Iraqi Journal of Veterinary Medicine, 2022)
Bovine mastitis is a disease that concerns animals’ welfare and increases the economic production losses. Bacterial agents such as Staphylococcus species are the main causative agent of bovine mastitis. This bacterial agent expresses some inflammatory cytokines that might enhance the cell-mediated, which may promote the pathogenesis of mastitis. The objective of the current study was to investigate the bovine innate immune response circulating levels of pro-inflammatory and anti-inflammatory cytokines. A total of 10 mL of milk specimens were collected randomly from 100 clinically mastitic cows, and another 20 clinically healthy cows were considered as a control group for the California Mastitis test. The microbiological cultures of milk specimens were performed. The interleukins (ILs)that involved IL-4, IL-6, and IL-10 were detected using the ELISA test for the evaluation of the pro-inflammatory bovine mastitis pathophysiology. The results of this study showed that Staphylococcus aureus detection was in 31.2% of mastitic milk and 8.7% of non-mastitic milk specimens; and the coagulase-negative Staphylococcus was detected in 14.8% and 18.7% in the mastitic and non-mastitic milk specimens, respectively. The IL-6 level was shown significantly higher (P<0.05)in the specimens of mastitic milk (194±12.8 pg/mL) compared to the non-mastitic milk (31±2.9 pg/mL). In conclusion, the elevated level of expression of IL-6 cytokine in the milk of cows with mastitis suggested that IL-6 might be used as a potentially suitable biomarker for early bovine mastitis diagnosis